A Descriptive Analysis of Learning Motivation Taken From Laskar Pelangi Novel - Nur Muthmainnah (Register Journal, 2010)
This paper informs us some motifs that motivate someone learning something taken from Laskar Pelangi novel. There are four research problems proposed of Laskar Pelangi novel; what are the literary elements of Laskar Pelangi novel; what are the motivations in learning presented in the novel of Laskar Pelangi; what are the reasons of Andrea Hirata took the motivation of learning in Laskar Pelangi novel; what are the implications of Laskar Pelangi novel toward its readers. This research uses descriptive research in analyzing, collecting the data. After analyzing the novel Laskar Pelangi the writer draws some conclusions as follows: the novel uses some figurative language to express some expressions and describe something; its main character is Ikal. Laskar Pelangi tells us some motifs of learning. The motivations which are pointed out are to enrich knowledge, to reach dream, to win a competition, and so on. The reason Andrea Hirata took learning motivation as the theme of Laskar Pelangi novel are to break Melayunese stereotype, to motivate all learner to be motivated in learning, and so on. The implication of Laskar Pelangi story toward its reader are Laskar Pelangi story motivated reader to study abroad, Laskar Pelangi teaches reader to admire the life.Keywords: learning motivation; Laskar Pelangi ; literary elements